Effect of Length of Stay Abroad and the Salary Level to the Total of Remittances of Migrant Workers - ., Basrowi (International Journal of Economics, Business and Management Studies, 2019)
This study aims to describe the effect of length of stay abroad and income level partially and simultaneously to the number of remittances sent to the village of migrant workers. The research method used is an ex-post-facto method. The research was conducted in Pidada Village, South Rawajitu District, and Sukabakti Village, Aji Baru Building, Tulang Bawang Regency, Lampung Province in January-April 2016. Based on the research result it can be concluded that, 1) there is significant influence between the length of stay abroad of the number of remittances sent to the village of migrant workers, 2) there is a significant influence between the level of income abroad on the number of remittances sent to the to the village of migrant workers. 3) there is a significant influence between the length of stay abroad and the level of income together against the number of remittances sent to the village of migrant workers.